2012
DOI: 10.1371/journal.ppat.1002583
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Entry of Botulinum Neurotoxin A Hc Domain through Intestinal Crypt Cells and Targeting to Cholinergic Neurons of the Mouse Intestine

Abstract: Botulism, characterized by flaccid paralysis, commonly results from botulinum neurotoxin (BoNT) absorption across the epithelial barrier from the digestive tract and then dissemination through the blood circulation to target autonomic and motor nerve terminals. The trafficking pathway of BoNT/A passage through the intestinal barrier is not yet fully understood. We report that intralumenal administration of purified BoNT/A into mouse ileum segment impaired spontaneous muscle contractions and abolished the smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 89 publications
2
36
0
Order By: Relevance
“…Botulinum complexes formed by BoNT and associated nontoxic proteins (ANTPs) including haemagglutinin (HA) components have reported to pass across the epithelial barrier upon HA-mediated opening of intercellular junctions. BoNT/A seems to preferentially use specific subsets of intestinal cells such as crypt enteroendocrine cells to enter the intestinal mucosa (Couesnon et al, 2012). However, purified BoNT has also been shown to undergo transcytosis through intestinal epithelial cells without the help of HAs (Fujinaga et al, 1997;Maksymowych and Simpson, 1998;Park and Simpson, 2003;Maksymowych and Simpson, 2004;Nishikawa et al, 2004;Ahsan et al, 2005;Couesnon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Botulinum complexes formed by BoNT and associated nontoxic proteins (ANTPs) including haemagglutinin (HA) components have reported to pass across the epithelial barrier upon HA-mediated opening of intercellular junctions. BoNT/A seems to preferentially use specific subsets of intestinal cells such as crypt enteroendocrine cells to enter the intestinal mucosa (Couesnon et al, 2012). However, purified BoNT has also been shown to undergo transcytosis through intestinal epithelial cells without the help of HAs (Fujinaga et al, 1997;Maksymowych and Simpson, 1998;Park and Simpson, 2003;Maksymowych and Simpson, 2004;Nishikawa et al, 2004;Ahsan et al, 2005;Couesnon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work showed that the majority of toxin absorption occurs in the mouse upper small intestine [7,32]. One model for the transit of BoNTs suggests that the holotoxin itself can transcytose through the intestinal epithelium [33,34,35]. A second model for the BoNT absorption from the epithelium implicates the hemagglutin proteins (HA) in this process by binding cell surface receptors on the apical side, transcytosis, and potential disruption of the epithelial barrier at the basolateral side to allow for paracellular transport of the toxins in certain situations [33,36].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps by increasing the photon yield of fluorescent ligands bound to the BoNTx/A heavy chain, or to its receptor in nerve terminal membranes, will enable this attractive molecular target to be exploited more effectively and to achieve its full potential for applications to CEM imaging. Quantum yield of fluorescence could be increased by uniting HcBoNTx/A with other conjugates 66. Alternatively, targeting fluorescent ligands to other receptors in presynaptic terminals could improve the contrast and intensity of the motor nerve terminal fluorescence.…”
Section: Discussionmentioning
confidence: 99%